2013 Kansas Performance Tests with Corn Hybrids - Lingenfelser, Jane (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2015)
Corn performance tests, conducted annually by the Kansas Agricultural Experiment Station, provide farmers, extension workers, and seed industry personnel with unbiased agronomic information on many of the corn hybrids marketed in the state. Because entry selection and location are voluntary, not all hybrids grown in the state are included in tests, and the same group of hybrids is not grown uniformly at all test locations. Contributors Main Station, Manhattan Jane Lingenfelser, Assistant Agronomist (Senior Author) Doug Jardine, Extension Plant Pathologist Jeff Whitworth, Extension Entomologist Mary Knapp, KSU Weather Data Librarian Edward O. Quigley, Agricultural Technician Experiment Fields Eric Adee, Topeka Gary Cramer, Hutchinson James Kimball, Ottawa Michael Larson, Scandia Wendell Lilyhorn, Hutchinson Randall Nelson, Scandia Keith Thompson, Hutchinson Research Centers Wayne Aschwege, Hays DeWayne Bond, Tribune Patrick Evans, Colby Kelly Kusel, Parsons Alan Schlegel, Tribune Monty Spangler, Garden City Cooperators Gene Eidman, Strong City Fuhrman Farms, Severance Lance Rezac, Onaga Norman Schmidt, Inman Clayton Short, Assaria Justin Vosburgh, Macksville
Keywords: Corn; Yields; Kansas; Disease; Weather; Insects; Statistics